2018
DOI: 10.1108/arj-09-2016-0109
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and Islamic banks’ products and services disclosure

Abstract: Purpose The purpose of this paper is to examine the determinants of Islamic banks (IBs) product and services disclosure (PSD). Design/methodology/approach A computer-based content analysis is run upon the annual reports for a sample of 78 IBs operating in 11 countries from 2004 to 2012 to find the number of product and services statements. The levels and trends of PSD are identified. A regression analysis to identify the factors affecting PSD in IBs is also used. Findings The findings suggest that there has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 26 publications
(34 reference statements)
7
52
0
1
Order By: Relevance
“…Also, Albassam and Ntim (2017), Mokhtar and Mellett (2013) and 2008) find no association between block ownership and level of risk disclosure in large listed non-financial firms. Finally, the findings of other past studies such as Grassa et al (2018) and Neifar and Jarboui (2018) found that ownership concentration has a positive impact on Islamic banks (IBs) product and services disclosure, and operational risk disclosure in a sample of IBs, respectively. We follow the main literature that found a negative relation between block ownership and level of risk disclosure and therefore, our study sets the following hypothesis, which states that: H2: There is a significant negative link between block ownership and the level of ORDs in MENA Islamic banks.…”
Section: Ownership Structure Board Mechanisms and Ordsmentioning
confidence: 51%
“…Also, Albassam and Ntim (2017), Mokhtar and Mellett (2013) and 2008) find no association between block ownership and level of risk disclosure in large listed non-financial firms. Finally, the findings of other past studies such as Grassa et al (2018) and Neifar and Jarboui (2018) found that ownership concentration has a positive impact on Islamic banks (IBs) product and services disclosure, and operational risk disclosure in a sample of IBs, respectively. We follow the main literature that found a negative relation between block ownership and level of risk disclosure and therefore, our study sets the following hypothesis, which states that: H2: There is a significant negative link between block ownership and the level of ORDs in MENA Islamic banks.…”
Section: Ownership Structure Board Mechanisms and Ordsmentioning
confidence: 51%
“…The legitimacy theory supports companies to generate and execute voluntary social and environmental disclosures to legitimize their presence and operations (Lindblom, 1994), while agency theory is used to resolve conflicts of interest between principals (shareholders) and their agents (managers) and confirms that managers are inclined to disclose gladly in the presence of adequate incentives for them (Haniffa & Cooke, 2002). Based on the stakeholder-agency theory, agency conflicts are relieved when decisions of managers about voluntary disclosure are aligned with the interest of all stakeholders (Grassa, Chakroun, & Hussainey, 2018). From the agency theory perspective, executive directors are agents of the shareholders, while nonexecutive and independent directors owe the shareholders a fiduciary duty that pushes the BOD to disclose more corporate news voluntarily to reduce information asymmetry (Gul & Leung, 2004).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Variabel profil DPS diukur dengan indikator jumlah DPS; rata-rata latar belakang pendidikan DPS (Skor 3 jika memiliki latar belakang ekonomi syariah, skor 2 jika memi liki latar belakang ekonomi atau hukum Is lam, dan selain itu diberi skor 1); rata-ra ta tingkat pendidikan DPS (doktor diberi skor 3, magister diberi skor 2, dan lainnya diberi skor 1) dan rasio DPS yang memili ki pendidikan doktor. Indikator ini dikem bangkan dari penelitian Farook, Hassan, & Lanis (2011), Grassa, Chakroun, & Hussainey (2018) Setiawan, Panduwangi, & Sumintono (2018). Variabel ukuran bank syariah diukur dengan menggunakan jum lah aset perusahaan.…”
Section: Metodeunclassified